Digitisation in European Libraries: Results of the NUMERIC Project - Poll, Roswitha (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2010)
NUMERIC, a project of the European Commission, started out to define units of measurement and methods for assessing the current state of digitisation in Europe’s cultural institutions (archives, libraries and museums). The aim was to show on the one side the financial input into digitisation and on the other side the progress achieved in digitising the national heritage. The article describes methods and results of the project, with special consideration to libraries.